Cost-effectiveness of newer technologies for the diagnosis of Mycobacterium tuberculosis infection in Brazilian people living with HIV - Steffen, Ricardo E.; Pinto, Marcia; Kritski, Afranio; Trajman, Anete (Scientific reports, 2020)
Tuberculosis is the leading cause of death among people living with HIV (PLH). Preventive tuberculosis therapy reduces mortality in PLH, especially in those with a positive tuberculin skin test (TST). New, more specific technologies for detecting latent tuberculosis infection (LTBI) are now commercially available. We sought to analyse the cost-effectiveness of four different strategies for the diagnosis of LTBI in PLH in Brazil, from the Brazilian public health care system perspective. We developed a Markov state-transition model comparing four strategies for the diagnosis of LTBI over 20 years. The strategies consisted of TST with the currently used protein purified derivative (PPD RT 23), two novel skin tests using recombinant allergens (Diaskintest [Generium Pharmaceutical, Moscow, Russia] and EC [Zhifei Longcom Biologic Pharmacy Co., Anhui, China]), and the QuantiFERON-TB-Gold-Plus (Qiagen, Hilden, Germany). The main outcome was cost (in 2020 US dollars) per quality-adjusted life years (QALY). For the base case scenario, the Diaskintest was dominant over all other examined strategies. The cost saving estimate per QALY was US $1375. In sensitivity analyses, the Diaskintest and other newer tests remained cost-saving compared to TST. For PLH, TST could be replaced by more specific tests in Brazil, considering the current national recommendations.